PSORIASIS PUSTULARIS DALAM KEHAMILAN - Dovy Djanas; Djusar Sulin (Universitas Andalas, 2019)
Psoriasis is a residual chronic inflammatory skin disease, characterized by a predominance of pustular eruptions accompanied by systemic symptoms such as fever lasting several days. . Psoriasis in pregnancy can lead to spontaneous abortion, stillbirth and preterm birth. Reported the case of Mrs. YS 38 years old, received from the genital skin section of RS M Djamil Padang with a diagnosis of G3P2A0H2 + pustular psoriasis. Fetomaternal ultrasound was performed, obtained biometrics: BPD: 80mm, FL: 61 mm, HL: 54 mm, AC 271 mm, AFI 10.7 cm, SDAU 2.79, estimated fetal weight 1700-1800 grams. Impression: gravid 31-32 weeks, single live fetus intra uterine. Patients are planned for administration of high doses of corticosteroids. Informed consent to the patient and family about the actions to be performed. Corticosteroid was administered as much as 30 mg long term with a dose of prednisone in tappering off every 2 weeks. The patient was discharged for control to the skin clinic and obstetrics, the patient came 12 days later and was consulted to the obstetrics department for termination of the pregnancy but from the obstetrics department there was no confirmation for termination of the pregnancy. The patient then came 13 days later with 18 hours PRM. Pregnancy termination by cesarean section was performed. a baby girl was born with LBW: 3000 gr, PB: 48 cm, A / S: 8/9, there were no congenital abnormalities such as growth disorders, cleft lip, cataracts, and polycystic kidney disease in infants. The cause of psoriasis in this case is probably pregnancy.Keywords: pustularis psoriais, psoriasis, pregnancy, corticosteroid